Bank Income Diversification from Stock Market Perspective: Evidence from ASEAN+3 - Natalia, Agnes Helena; Kurniawan, Muchamad Rudi; Firsty, Revinska R. (UI Scholars Hub, 2016)
This paper empirically examines the effect of banks' revenue diversification on the stock-based return and risk measures using data on the ASEAN-5, and addition from China, Japan, and South Korea banking sector. This paper use panel Fixed Effect and robustness test with Random Effect and TSLS. We use non-interest income share as a measure for revenue diversification. We find that revenue diversification has no effect on bank market value but significantly decrease bank total risks. When non-interest income is decomposed, we find that fee-income business has significant positive effect on bank value. Furthermore, it’s important to see characteristic of banks that do diversification, such as bank size and capital. Overall, we give evidence that banks, especially which have big size and good condition on capital, could increase their value and lower their risk by doing diversification in income through non-interest income, especially with fee income and other non-interest income